Media Digitalization in Improving the Image of Local Wisdom Based Tourism Villages in the City of Semarang - Mubarok, Fikri Shofin; Nurkholis, Nurkholis (Jurnal Ilmiah Komunikasi Makna, 2024)
The city of Semarang, as the capital of Central Java Province, has great tourism potential. There are various forms of tourism there, ranging from nature tourism to historical tourism, wildlife tourism, religious tourism, and others. Several tourist villages in the city of Semarang have been built, but their marketing is still not optimal. So the target number of tourist visits to the tourist village is still not as expected. In fact, various forms of tourist objects and villages can contribute to improving the economy of the surrounding community and Semarang City's locally generated revenue. To achieve this target, a digital-based tourism promotion strategy is needed. So here we will examine the urgency of media digitalization in order to improve the image of local wisdom-based tourist villages with a case study in the Kandri Tourism Village. This study uses a qualitative research method with a descriptive approach chosen to clearly explain the strategy for developing media digitalization to improve the image of local wisdom-based tourist villages in Semarang City. The data collection technique uses interviews and direct observation with informants in the Kandri Tourism Village. Then the research results showed that tourism based on local wisdom and the active role of the community were initiated by the Kandri Tourism Village Pokdarwis in packaging creative digital tourism promotions that could increase tourist visits. The right digital branding of Dewi Kandri is able to increase the positive image of the Kandri tourist village in the eyes of the public as a local wisdom-based tourist destination in Semarang City.